Stability of phosphatidylethanol species in spiked and authentic whole blood and matching dried blood spots - Stadler, Andrea; Richter, Barbara; Kluge, Matthias; Koenig, Patrick; Seitz, Helmut K.; Skopp, Gisela (International journal of legal medicine, 2013)
BACKGROUND: Phosphatidylethanol (PEth) is currently under investigation as a highly sensitive and specific marker of alcohol misuse. As its stability in blood samples has not systematically been investigated, a study was performed to determine the stability of major PEth species in spiked and authentic whole blood and also in matching dried blood spots (DBS) at different conditions. - METHODS: To PEth-free blood from teetotalers, low and high concentrations of two major PEth (18:1/18:1 and 16:0/18:1) species were added chosen on the basis of concentrations determined from authentic samples which were collected from the subjects undergoing alcohol detoxification treatment. Effects of sampling (EDTA or heparinized tubes), temperature, and time (≤30 days) were investigated. Processed samples (two at each condition, respectively) were subjected to LC gradient separation using multiple reaction monitoring. Stability was assessed using the critical difference or a periodic analysis result that was within 15 % of the initial concentration. Reaction kinetics of degradation was investigated with rate constants being checked for an Arrhenius relationship. - RESULTS: PEth was stable in dried blood spot (DBS) stored either at room temperature or frozen, whereas it was not stable in whole blood except in samples stored at -80 °C. Activation energies increased in the following order: spiked heparinized blood < spiked EDTA blood < authentic EDTA blood. - CONCLUSIONS: PEth is a labile analyte which is predominantly degraded by hydrolysis. Only at -80 °C, stability in whole blood can be ascertained, and analysis should be performed within 30 days. EDTA should be preferred over heparin as an additive. DBS is able to stabilize PEth thus partly resolving pre-analytical difficulties of PEth measurement.
Published online: 4 December 2012
Gesehen am 25.02.2021